2009 IEEE Globecom Workshops 2009
DOI: 10.1109/glocomw.2009.5360722
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Multipoint Trials in the Downlink

Abstract: Abstract-Coordinated multi-point (CoMP) is a new class of transmission schemes for interference reduction in the next generation of mobile networks. We have implemented and tested a distributed CoMP transmission approach in the downlink of an LTE-Advanced trial system operating in real time over 20 MHz bandwidth. Enabling features such as network synchronization, cell-and user-specific pilots, feedback of multicell channel state information and synchronous data exchange between the base stations have been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Ergodicity describes that any sample that belongs to a process is representative of the entire process, statistically-wise [11]. It is noticed that when the SNR decreases, channel capacity increases.…”
Section: Resultsmentioning
confidence: 99%
“…Ergodicity describes that any sample that belongs to a process is representative of the entire process, statistically-wise [11]. It is noticed that when the SNR decreases, channel capacity increases.…”
Section: Resultsmentioning
confidence: 99%
“…The semi-distributed architecture, introduced in [29] and [30], is depicted in Figure 3. Under this architecture, each user feeds back the CSI vector to its serving TN.…”
Section: Semi-distributed Comp Architecturementioning
confidence: 99%
“…e Note that shadowing can be introduced to our model by adding a shadowing factor to each of the (d) values in Equation 29.…”
Section: Endnotesmentioning
confidence: 99%
“…3 turned out as an essential enabler for CoMP trials in the field where we use distributed MT and BS locations. In our previous trials [22], the CSI feedback from both MTs has been decoded at each BS. Note that channel gains and delays between the distributed BSs and MTs in the field can vary substantially.…”
Section: B Csi and Data Exchange Networkmentioning
confidence: 99%
“…Implementation of enabling features such as clock synchronization, synchronous data exchange, cell specific pilots, CSI feedback, cooperative precoding, precoded pilots and initial laboratory trials are reported in [22]. Here we describe further system extensions enabling over-the-air experiments with physically separated BSs and distributed mobile terminals (MTs) and report initial field trial results.…”
Section: Introductionmentioning
confidence: 99%